2012
DOI: 10.1177/1477370812459823
|View full text |Cite
|
Sign up to set email alerts
|

Crime and criminology in Sweden

Abstract: Background Sweden is a sparsely populated country of 9 million people, geographically located on the margins of the European Union (EU). Approximately one-third of the population lives in the three metropolitan areas of Stockholm, Göteborg and Malmö, and around 14 percent of Sweden's population are born overseas. Sweden is often described, together with Denmark, Finland, Iceland and Norway, as a welfare country characterized by low levels of income inequality (Lappi-Seppälä and Tonry, 2011). Prior to an electi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…In the United States, evidence has shown increases in parent‐, teacher‐ and self‐rated conduct problems between the 1970s and 1980s, followed by a fall in the 1990s (Achenbach, Dumenci, & Rescorla, , ; Achenbach et al., ). In Sweden, there is evidence for an increase in self‐reported offending and conduct problems in adolescent cohorts between 1970 and 1996 (Wångby et al., ), followed by a decline in antisocial behaviour since the 1990s consistent with national trends in registered crime (Backman, Estrada, Nilsson, & Shannon, ; Estrada, Petterson, & Shannon, ). Evidence for an increase in behaviour problems, at least for girls, has also been reported in China between 1993 and 2003 (Lin & Wang, ).…”
Section: Trends In Child and Adolescent Mental Healthmentioning
confidence: 93%
“…In the United States, evidence has shown increases in parent‐, teacher‐ and self‐rated conduct problems between the 1970s and 1980s, followed by a fall in the 1990s (Achenbach, Dumenci, & Rescorla, , ; Achenbach et al., ). In Sweden, there is evidence for an increase in self‐reported offending and conduct problems in adolescent cohorts between 1970 and 1996 (Wångby et al., ), followed by a decline in antisocial behaviour since the 1990s consistent with national trends in registered crime (Backman, Estrada, Nilsson, & Shannon, ; Estrada, Petterson, & Shannon, ). Evidence for an increase in behaviour problems, at least for girls, has also been reported in China between 1993 and 2003 (Lin & Wang, ).…”
Section: Trends In Child and Adolescent Mental Healthmentioning
confidence: 93%
“…In Sweden, the tendency of schools to treat unruly behaviour, bullying and violence as crimes is partly a new phenomenon. Compared with most European countries and the US, Sweden has been viewed as an exception, focusing on care and social pedagogical measures instead of punishment (Estrada, Pettersson, & Shannon, 2012). Furthermore, Sweden has long been known for its progressive ideals and great emphasis on equality (Englund, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also shown how contextual factors in the neighbourhood influence students' risk of encountering crime or their inclination to commit crime (Gottfredson & DiPietro, 2011). Further, studies have revealed that, among both victims and offenders, there is an overrepresentation of children growing up in socio-economically disadvantaged circumstances and neighbourhoods (Estrada et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there has been a development whereby behavior previously categorized as fights and teasing in various policy documents is now described using a legal discourse, such that juridical concepts like discrimination and harassment are used (Swedish National Agency for Education, 2011). One result of this is that the number of police reports has increased (Estrada et al, 2012). At the same time, there is no clear evidence that violence and degrading treatment are actually increasing in Swedish schools.…”
Section: Introductionmentioning
confidence: 99%